Comparison between the levels of Pentraxin-3 and soluble lectin like oxidized LDL receptor-1 in rheumatoid arthritis patients - Esmat, Sura Abdul Kareem (International Journal of Psychosocial Rehabilitation, 2020)
Rheumatoid arthritis can defined as autoimmune disease that characterized by inflammatory synovitis, joint pain and functional disability and this can lead to destruction in the articular cartilage and bone. Our objective is to assess serum level of sLOX-1 and PTX-3 in patient with rheumatoid arthritis (Study design: Case control study). Eighty four people were included in this study, all from AlYarmook Teaching Hospital during period from December 2019 to February  2020 Subjects were divided into three groups:1- Control group (non- patient group): involve 28 healthy subjects  2-Patient study group 1: involve 28 subjects suffering from mild sign of Rheumatoid arthritis.3- Patient study group 2: involve 28 subjects suffering from severe sign of Rheumatoid arthritis. All patients were diagnosed with Rheumatoid arthritis have tender, warm, swollen joints with joint stiffness usually in the morning or after period of inactivity with fatigue, fever and loss of appetite. Mild cases is tend to be affect the smaller joints like fingers , hand and toes of feet and severe cases the sign spread to wrist, knee, elbow, hips and shoulders.. Serum samples were analyzed by using (ELISA). There was significantly increasing in mean level of sLOX-1and PTX-3, it was significantly higher in severe RA patient group than mild RA patient group and healthy control group (P